The Code of Ethics and Disciplinary Management of Political Parties Member - Kausar Jumahir Lesen; Muhtadi Muhtadi; Martha Riananda (Constitutionale, 2022)
Violation of the law which includes ethical violations is actually an act contrary to the ethical rules of regulations for members of political parties. Still, these violations indicate an increase in public officials from political parties. As such, it is interesting to research how to determine the model of the code of ethics for members of political parties. It includes members of political parties who are involved as well as public officials. The type of research used in this article is normative-empirical with a statutory approach and is supported by field research. The data obtained were then analyzed qualitatively. The results of the research and discussion show that the enforcement of the code of ethics and party discipline is carried out through prevention and prosecution efforts. Prevention efforts are carried out through continuous guidance for ordinary members, members, and party cadres by the party honors division at each level of the party leadership council. Meanwhile, efforts to take action are carried out by the party ethics and disciplinary committee formed by the DPP, which is tasked with examining and proving any alleged violations of the party's code of ethics and discipline by party members. The party ethics and disciplinary committee is authorized to examine and provide recommendations on whether party members are guilty of violating the code of ethics and/or party discipline on the basis of reports, complaints, or information.